HUBUNGAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) DENGAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA PEKERJA KILANG PADI - Reni Aprinawaty Sirait; Vina Novianti; Luci Riani Br Ginting (JURNAL KESMAS DAN GIZI (JKG), 2020)
Respiratory Protection Equipment (APD) is a set of tools used by workers to protect all or part of their body from the possibility of potential occupational hazards such as ISPA (Upper Respiratory Infection) in Rice Refinery Workers in Dalu X-B Village, Tanjung Morawa Sub-District, Deli Serdang Regency. The number of patients with ARI in 2015 was found to be 452 cases and increased in 2016 by 469 cases. The use of respiratory protective equipment is often considered unimportant or trivial by workers, especially in workers who work in the informal sector. Every worker needs to wear respiratory protective equipment especially workers whose work environment contains a lot of dust so workers must be obliged to use a complete respiratory protective device when doing work because to maintain personal safety and personal health while working. This research was used analytic survey method by using cross sectional design. Samples were taken as many as 62 workers with sampling techniques using total sampling. This research was carried out in two rice milling industries in the village of Dalu XB, Tanjung Morawa District, Deli Serdang District. The data collection was carried out by direct interview using a questionnaire to find out the data of the age of the workers, long work, and education level. Data analysis performed was univariate and bivariate with statistical tests using the Chi Square test with Î± = 0.05. With the results there was a relationship between the use of respiratory protective equipment with the incidence of acute respiratory infections (ISPA) in Rice Refinery Workers in Dalu X-B Village, Tanjung Morawa District, Deli Serdang District in 2017 with pValue (= 0.01) â‰¤ Î± (= 0.05). For rice refinery workers must be able to comply with regulations that have been determined in the use of masks and Rice refinery workers.